MANAJEMEN STRATEGI DALAM MENINGKATKAN DAYA SAING PENDIDIKAN - Rukmanasari, Sulistya Umie (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
Competition as the main feature of modern civilization has evolved as solid mastery of information and communication technologies are innovative and varied. The competitiveness is one very important advantage for an organization, competitiveness is not only a strength but more than that is the consistency in order to withstand the increasingly fierce competition. So to be the winner in providing educational services required analysis of competitiveness and the implementation of appropriate strategies and superior to win the competition. There are several techniques that can be used in analyzing the competitiveness in the world of education, namely to make: (1) the SWOT matrix; (2) matrix SPACE; and (3) the BCG matrixÂ Keywords: strategic management, competitiveness, education